How to evaluate supply chain risks, including sustainable aspects? A case study from the German industry - Rubén Medina-Serrano; Reyes González-Ramírez; José Gascó; Juan Llopis (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: Outsourcing transactions have been arisen and evolved in the last years and purchase managers want to know if a Failure Mode Effects and Analysis (FMEA) is an effective qualitative technique to analyze supply chain risks (SCR) in a proper way. The aim of this study is to address this question developing a practicable risk management process based on the guidelines of the ISO 31000 for upstream Supply Chain Risk Management (SCRM) linking risk assessment, risk identification, risk analysis, risk evaluation, risk treatment and validate the process empirically through a case study. Design/methodology/approach: After a review of the literature on Sustainable Supply Chain Risk Management (SSCRM), a case study based on a leading manufacturer of electrical products, collects evidences of SSCRM implementation. Findings: Supply chain disruptions are one of the most critical issues which can negatively influence on firm's performance. Avoiding and mitigating disruptions in the supply chain is one of the main challenges for supply chain managers. Originality/value: This paper identifies the ISO 31000, the ISO 9001 and the use of an FMEA to analyze supply chain risks in a structured manner and to outline future research opportunities in the field of SCRM.
Keywords: 650; supply chain risk management (SCRM); ISO 31000; ISO 9001; failure mode effects and analysis(FMEA); case study